Homologs of the Brugia malayi diagnostic antigen BmR1 are present in other filarial parasites, but induce different humoral immune response - Aziz, Ros Azeana Abdul; Noordin, Rahmah; Ravindran, Balachandran (Penerbit Universiti Sains Malaysia, 2004)
Lymphatic filariasis, caused by Brugia malayi and Brugia timori, is endemic in several Asian countries and infects ~ 13 million people. The WHO initiated Global Program for Elimination of Lymphatic Filariasis (GPELF) aims to eliminate the disease as a public health problem by the year 2020.